2019
DOI: 10.5222/head.2019.176
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Nurses’ Knowledge and Practice about the Temperature of Milk Fed to Infants: A Descriptive Study

Abstract: Amaç: Yenidoğan yoğun bakım ünitesinde çalışan hemşirelerin bebeklere verdikleri süt ısısına ilişkin uygulama ve bilgilerini değerlendirmektir. Yöntem: Araştırma 116 yenidoğan yoğun bakım hemşiresi ile yapılmıştır. Veriler Hemşireyi Tanıtıcı Bilgi Formu ve Hemşirelerin Süt Isısına İlişkin Uygulama ve Bilgileri Anketi ile toplanmıştır. Bulgular: Katılımcıların %52.6'sının bebeklere verilen anne sütü/formül süt ısısının 35°C'nin altı, %47.4'ü 35°C'nin üstü olması gerektiğini ve %76.4'ü bebeklere verilen sütün ıs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…This result due to the many numbers of nurses' dependent on the head nurse to regulate the refrigerator's temperature. This result differs with özçelik & Aktaş [9] who studied ''The Evaluation of Nurses' Knowledge and Practice about the Temperature of Milk Fed to Infants: A Descriptive Study'' and reported that the nurses had insufficient knowledge regarding the proper temperature of the breast milk.…”
Section: Discussioncontrasting
confidence: 71%
“…This result due to the many numbers of nurses' dependent on the head nurse to regulate the refrigerator's temperature. This result differs with özçelik & Aktaş [9] who studied ''The Evaluation of Nurses' Knowledge and Practice about the Temperature of Milk Fed to Infants: A Descriptive Study'' and reported that the nurses had insufficient knowledge regarding the proper temperature of the breast milk.…”
Section: Discussioncontrasting
confidence: 71%